Combined Effect of Physical and Psychological Stress Exposure during Pregnancy on the Expression of Caspase-3 Cerebrum and Cerebellum of Newborn Mus Musculus - Binta Dwi Novitasari; Hermanto Tri Joewono; Widjiati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Prenatal stress affects fetal development including brain development. When a stressor isfelt, the brain as the main target for stress will release a hormone that stimulates the release of pro-apoptoticproteins and activate caspase-3 which acts as an executioner caspase in the cell death process. The aim of thestudy was to analyze the effect of combined stress during pregnancy on the expression of caspase-3 cerebrumand cerebellum of newborn Mus musculus. Methods: An experimental study using 24 pregnant mice (Musmusculus). Subjects were randomized into four groups, consisting of physical stress exposure group (forcedswimming) (G1), psychological stress exposure group (noise) (G2), combination stress exposure group(forced swimming + noise) (G3), and control group (G4). Stress exposure was given on 6th-15th days ofpregnancy. From each mother, three Newborn of Mus musculus were taken to make preparations from braintissue. Immunohistochemical examination was performed to assess caspase-3 expression. Results: Thestudy shows that the mean and standard deviation of the expression of caspase-3 cerebrum and cerebellumin the physical stress exposure group is 5.70 ± 0.99 and 5.80 ± 1.35, the psychological stress exposure groupis 7.23 ± 1.39 and 7.40 ± 1.24, the combined stress exposure group is 8.67 ± 1.09 and 9.30 ± 1.12, and thecontrol group 4.17 ± 1.18 and 3.90 ± 1.06. ANOVAs statistical test results show significant differencesamong groups with a value of p = 0.000 in the cerebrum and p = 0.000 in the cerebellum. Conclusion:Exposure to physical and psychological stress during pregnancy increases the expression of caspase-3 in thecerebrum and cerebellum of newborn mice.